2016
DOI: 10.1007/s10461-016-1497-4
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprick Versus Oral Swab: Acceptability of Blood-Based Testing Increases If Other STIs Can Be Detected

Abstract: Self-testing has untapped potential as a strategy to improve access to HIV testing and to increase testing frequency. User acceptability of self-administered oral swab HIV tests is consistently high in both hypothetical and actual-use studies. We explored preferences for oral versus fingerprick HIV self-tests among men who have sex with men (MSM) with a high risk profile. Participants indicated greater likelihood of using an oral swab over a blood-based test, notwithstanding lower price or quicker results from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 12 publications
(20 reference statements)
1
21
0
Order By: Relevance
“…Besides urine samples and anorectal and oropharyngeal swabs, the test kit included a blood sample to test for syphilis and HBV. Our study confirmed that most MSM considered finger prick blood sampling feasible and acceptable based on the previous studies [23,24].…”
Section: Discussionsupporting
confidence: 88%
“…Besides urine samples and anorectal and oropharyngeal swabs, the test kit included a blood sample to test for syphilis and HBV. Our study confirmed that most MSM considered finger prick blood sampling feasible and acceptable based on the previous studies [23,24].…”
Section: Discussionsupporting
confidence: 88%
“…A variety of statistical approaches were used in these studies, most commonly logistic regression (13, 39%) [ 73 85 ] and Chi squared tests (including Pearson’s and Fisher’s exact) (12, 36%) [ 24 , 25 , 73 , 75 , 80 , 83 , 86 – 91 ]. T-tests (5, 15%) and analysis of variance (4, 12%) [ 24 , 86 , 88 , 91 ] were also employed, as well as types of regression (linear [ 92 , 93 ], count [ 94 ], log binomial [ 95 ], ordinary least squares [ 96 ], and logit link [ 97 ]). Three studies used Mann–Whitney U tests (9%) [ 81 , 93 , 98 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies investigated combinations of voluntary testing and counseling product and service design [ 24 , 28 , 44 , 45 , 50 , 53 55 , 86 , 88 , 93 , 95 , 96 , 99 , 102 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study in Vietnam MSM and female sex workers (FSW) preferred oral fluid HIVSTs, while injection drug users (IDU) preferred blood based kits (25). In work from the US conducted with an ethnically diverse group of high risk MSM, more frequent testers preferred blood based testing, whereas men who tested less frequently preferred oral fluid HIVSTs (35).…”
Section: Understanding Implementation Contexts: Values and Preferencesmentioning
confidence: 99%